Sistem Pemilihan Perumahan dengan Metode Kombinasi Fuzzy C-Means Clustering dan Simple Additive Weighting - Jaya, Tri Sandhika; Adi, Kusworo; Noranita, Beta (Universitas Diponegoro, 2011)
Housing is one of human secondary needs. In selecting the most appropriate housing, there are lots of aspects to be considered to satisfy the costumers want. In order to get optimal result, a system is needed to help the costumers to decide which housing fit them most. System that will be built in this thesis is a system that supports costumers’ satisfaction in housing selection. There are 2 main stages in the system, namely data grouping and ranking. Data grouping method used is Fuzzy C -Means Clustering (FCM). Simple Additive Weighting (SAW) is used for ranking purpose. Testing is carried out by comparing interview result with system counting result. The testing result produces 9 cases that derive similar recommendation.Keywords : Housing selection; FCM; SAW; Recommendation; Grouping